EFFECT OF CALAMANSI CITRUS (Citrus microcarpa) EXTRACTS AND CMC TO PREFERENCES OF RED PALM OIL EMULSIONS - Budiyanto Budiyanto; Bosman Sidebang; Rut Rae Delima Samosir (Jurnal Agroindustri, 2019)
The purpose of this research were to obtain amount of the addition of calamansi citrus extract and CMC in the produce stable red palm oil emulsions with optimal viscosity and to obtain red palm oil emulsion products that can neutralize chelate taste and cover the oils aroma based on the level of consumer preferences. A complete randomized design (CRD) with two factorial was employed. The factors used were the amount of calamansi citrus extracts  addition (5 gram, 7 gram and 9 gram) and the amount of CMC addition (1 gram and 1.5 gram) . Data in this research obtained from the observations and results of viscosity and organoleptic testing were processed used analysis of variance (ANOVA) and a further test using DMRT on SPSS software. The results showed that the addition of calamansi citrus extract and CMC has significant effect to the stability and viscosity, but no significant effect to the taste, aroma and color of red palm oil emulsions product. Overall the best preferences of the emulsion product is the red palm oil emulsions with the addition of 7 grams calamansi citrus extract and 1 gram CMC. The emulsion product best stability is the red palm oil emulsions with the addition of 5 gram calamansi citrus extract and 1.5 gram CMC for 12 days. However, the emulsion product having a stability for 12 days but it has a viscosity of 1468.42 cP so further research is needed to reduce the emulsion viscosity. Keywords : red palm oil emulsions,calamansi citrus extract, CMC